Study on the electro-optical properties of epoxy resin based polymer dispersed liquid crystal films. Issue 1 (22nd November 2021) - Zhao, Yuzhen; He, Zemin; Ban, Quanzhi; Li, Kexuan; Ding, Siyi; Tian, Shaopeng; Ren, Huaping; Zhu, Min; Ma, Qiang; Miao, Zongcheng
Abstrat: Polymer dispersed liquid crystal (PDLC) films have been extensively studied for their ability to control the attitude of aircraft by varying the reflectivity of solar sails. However, most of the polymeric matrix of PDLC films are based on polyacrylates, which comprehensive properties such as thermal stability, chemical stability, mechanical strength and radiation resistance can not meet the requirements of the harsh environment in space. In order to improve the radiation resistance of PDLC films, polyimide-epoxy resin PDLC films were prepared by thermal polymerization using Kapton polyimide film as conductive film and two kinds of epoxy resin as monomer in this paper. The electro-optic properties of PDLC films prepared by flexible chain and rigid chain epoxy resin monomers in different ratios were studied and the microscopic morphology of the polymer network of the polyimide PDLC films was observed by scanning electron microscopy (SEM) and the relationship between them was studied.